2014
DOI: 10.1039/c4dt00817k
|View full text |Cite
|
Sign up to set email alerts
|

α-Borylcarbonyl compounds: from transient intermediates to robust building blocks

Abstract: α-Borylcarbonyl species (C-bound boron enolates) are typically unstable due to their kinetic and thermodynamically favourable rearrangement to their O-bound isomers. Direct evidence of α-borylcarbonyl compounds is sparse despite the multitude of transformations in which they have been implicated as reactive intermediates. In recent years, a few examples have emerged of reactive α-borylcarbonyl intermediates that can be observed using spectroscopic methods. Other reports have shown that certain compounds contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…[7] Hence,t he formation of C-boron enolates (a-boryl carbonyls) provides ag reater challenge to the synthetic chemist. [8] However,t hey have potentially good synthetic value because they are kinetically amphoteric,m eaning that they contain an ucleophilic site adjacent to an electrophilic center (the nucleophilic boronate and the electrophilic carbonyl) and hence exhibit multiple modes of reactivity. [9]…”
mentioning
confidence: 99%
“…[7] Hence,t he formation of C-boron enolates (a-boryl carbonyls) provides ag reater challenge to the synthetic chemist. [8] However,t hey have potentially good synthetic value because they are kinetically amphoteric,m eaning that they contain an ucleophilic site adjacent to an electrophilic center (the nucleophilic boronate and the electrophilic carbonyl) and hence exhibit multiple modes of reactivity. [9]…”
mentioning
confidence: 99%
“…As part of our research program in chemical synthesis, we have developed air‐ and moisture‐stable α‐boryl aldehydes . In these compounds, premature reactivity between the nucleophilic and electrophilic functional groups is prevented through the use of N ‐methyliminodiacetic acid (MIDA).…”
Section: Introductionmentioning
confidence: 99%
“…[1, 2] With regards to enolizable carbonyls that can generate boron enolates,t here is ar apid equilibrium between the O-and Cbound forms,with the latter being much less thermodynamically stable because of the stronger OÀBb onds over CÀB bonds. [8] However,t hey have potentially good synthetic value because they are kinetically amphoteric,m eaning that they contain an ucleophilic site adjacent to an electrophilic center (the nucleophilic boronate and the electrophilic carbonyl) and hence exhibit multiple modes of reactivity. [8] However,t hey have potentially good synthetic value because they are kinetically amphoteric,m eaning that they contain an ucleophilic site adjacent to an electrophilic center (the nucleophilic boronate and the electrophilic carbonyl) and hence exhibit multiple modes of reactivity.…”
mentioning
confidence: 99%
“…[7] Hence,t he formation of C-boron enolates (a-boryl carbonyls) provides ag reater challenge to the synthetic chemist. [8] However,t hey have potentially good synthetic value because they are kinetically amphoteric,m eaning that they contain an ucleophilic site adjacent to an electrophilic center (the nucleophilic boronate and the electrophilic carbonyl) and hence exhibit multiple modes of reactivity. [9] Generally,the formation of stable,isolable a-boryl carbonyls remains an underexplored area of research, despite the fact that they have been suggested or (in some cases) shown to be implicated as reactive intermediates in many transformations.…”
mentioning
confidence: 99%